2016
DOI: 10.1038/srep27997
|View full text |Cite
|
Sign up to set email alerts
|

MRA_1571 is required for isoleucine biosynthesis and improves Mycobacterium tuberculosis H37Ra survival under stress

Abstract: Threonine dehydratase is a pyridoxal 5-phosphate dependent enzyme required for isoleucine biosynthesis. Threonine dehydratase (IlvA) participates in conversion of threonine to 2-oxobutanoate and ammonia is released as a by-product. MRA_1571 is annotated to be coding for IlvA in Mycobacterium tuberculosis H37Ra (Mtb-Ra). We developed a recombinant (KD) Mtb-Ra strain by down-regulating IlvA. The growth studies on different carbon sources suggested reduced growth of KD compared to wild-type (WT), also, isoleucine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Earlier studies suggested that the BCAA biosynthetic pathway plays a role in pH homeostasis and IlvC has even been observed to be up-regulated at low pH (5.0) in Streptococcus mutans [20] and IlvC inactivation led to growth retardation at pH=5.5 [33]. Reduced survival of IlvA KD Mtb -Ra was also observed at lower pH (5.5 and 4.5) [5] as well as in IlvC KD of Mtb -Ra, as in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies suggested that the BCAA biosynthetic pathway plays a role in pH homeostasis and IlvC has even been observed to be up-regulated at low pH (5.0) in Streptococcus mutans [20] and IlvC inactivation led to growth retardation at pH=5.5 [33]. Reduced survival of IlvA KD Mtb -Ra was also observed at lower pH (5.5 and 4.5) [5] as well as in IlvC KD of Mtb -Ra, as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The cloning and expression studies were performed as per published protocols [5] and are detailed in Supplementary Data S1 and Fig. S4.…”
Section: Methodsmentioning
confidence: 99%
“…Among the genes showing a slightly increased mRNA level in response to malR expression, we also found the ilvA gene, encoding a threonine-dehydratase that is necessary for the production of isoleucine (Sharma et al, 2016). Isoleucine is a branched chain amino acid and, together with acetyl-CoA, an important precursor for the generation of branched chain fatty acids, which are part of the bacterial cell membrane.…”
Section: Resultsmentioning
confidence: 89%
“…It was observed that ilvA knockdown (KD) strain in H37Ra exhibited impaired growth on isoleucine depleted media and against oxidative stress induced by H 2 O 2 and NO. Further, the ilvA KD modified cell wall lipid composition and was vulnerable to antibiotics such as streptomycin, levofloxacin and rifampicin 56 . Isoleucine is the final product of threonine degradation pathway.…”
Section: Enzymes Of Amino Acid Metabolism As Drug Targetsmentioning
confidence: 99%